Analisis Kinerja Belanja Daerah Pemerintah Provinsi Kalimantan Utara - Ferica Christinawati Putri (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
This research is a qualitative descriptive study with data collection using documentation techniques and the data used is in the form of Realization Reports of the Regional Revenue and Expenditure Budget of the North Kalimantan Provincial Government. Furthermore, this data is analyzed using financial ratios, namely the growth ratio and compatibility ratio. The results of the study show that there has been an increase in regional spending by the North Kalimantan Provincial Government and the calculation of the compatibility ratio shows that the Regional Government of North Kalimantan Province for the 2020 and 2021 Fiscal Years in allocating their funds for activities prioritizes operational spending, namely 72.19% and 80.35% the comparison is much greater with capital expenditure which is only 27.80% and 19.06%.